(untitled) (Communications in Mathematical Research, 2021)
In this article, we generalize Chebyshev's maximum principle to several variables. Some analogous maximum formulae for the special integration functional are given. A sufficient condition of the existence of Chebyshev's maximum principle is also obtained.